Atomic‐Scale Insights into the Low‐Temperature Oxidation of Methanol over a Single‐Atom Pt1‐Co3O4 Catalyst. (3rd June 2019) - Jiang, Zeyu; Feng, Xiangbo; Deng, Jianlin; He, Chi; Douthwaite, Mark; Yu, Yanke; Liu, Jian; Hao, Zhengping; Zhao, Zhen
Abstract: Heterogeneous catalysts with single‐atom active sites offer a means of expanding the industrial application of noble metal catalysts. Herein, an atomically dispersed Pt1 ‐Co3 O4 catalyst is presented, which exhibits an exceptionally high efficiency for the total oxidation of methanol. Experimental and theoretical investigations indicate that this catalyst consists of Pt sites with a large proportion of occupied high electronic states. These sites possess a strong affinity for inactive Co 2+ sites and anchor over the surface of (111) crystal plane, which increases the metal–support interaction of the Pt1 ‐Co3 O4 material and accelerates the rate of oxygen vacancies regeneration. In turn, this is determined to promote the coadsorption of the probe methanol molecule and O2 . Density functional theory calculations confirm that the electron transfer over the oxygen vacancies reduces both the methanol adsorption energy and activation barriers for methanol oxidation, which is proposed to significantly enhance the dissociation of the CH bond in the methanol decomposition reaction. This investigation serves as a solid foundation for characterizing and understanding single‐atom catalysts for heterogeneous oxidation reactions. Abstract : A single‐atom Pt1 ‐Co3 O4 material with strong metal–support interactions is designed, which exhibits excellent catalytic performance for methanol low‐temperature oxidation. The electron transfer over the oxygen vacancies reduces both the methanol adsorption energy and activation barriers for methanol oxidation, which is proposed to significantly enhance the dissociation of the CH bond in the combustion reaction.